Ionic solvation studied by image-charge reaction field method - Lin, Yuchun (American Institute of Physics, 2011)
In a preceding paper [J. Chem. Phys. 131, 154103 (2009)], we introduced a new, hybrid explicit∕implicit method to treat electrostatic interactions in computer simulations, and tested its performance for liquid water. In this paper, we report further tests of this method, termed the image-charge solvation model (ICSM), in simulations of ions solvated in water. We find that our model can faithfully reproduce known solvation properties of sodium and chloride ions. The charging free energy of a single sodium ion is in excellent agreement with the estimates by other electrostatics methods, while offering much lower finite-size errors. Similarly, the potentials of mean force computed for Na–Cl, Na–Na, and Cl–Cl pairs closely reproduce those reported previously. Collectively, our results demonstrate the superior accuracy of the proposed ICSM method for simulations of mixed media.